God, Human, and Nature: Ecological Theocentrism and the Asset-Based Formation of Environmental Consciousness in an Islamic Boarding School - Abdul Hanan; Saeful Anwar (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
This article examines how ecotheological consciousness is formed within an Islamic boarding school (pesantren) through the Asset-Based Community Development (ABCD) approach, and it corrects a conceptual error common in the Indonesian literature on Islamic ecology. That literature routinely describes the tawḥīdic reframing of nature as a shift from anthropocentrism to ecocentrism. The description cannot be sustained: khilāfa, amāna, and taskhīr are structurally anthropocentric concepts, and ecocentrism, in the sense given to it by Naess and Rolston, denies precisely the privileged human standing that those concepts presuppose. What a tawḥīdic reframing actually produces is not ecocentrism but ecological theocentrism — nature possesses value not autonomously but because it is God's creation, His sign (āya), and a participant in a cosmic praise that human beings do not comprehend. The article argues that this is a distinct and defensible third position, irreducible to the Western anthropocentrism–ecocentrism dichotomy, and that recognising it resolves a contradiction that has quietly disabled much Indonesian ecotheological writing. Empirically, the study reports a participatory engagement conducted over four months (September–December 2025) at Pesantren Al-Faruq (Bandung), using the five-stage Appreciative Inquiry cycle in its correct sequence (Define, Discovery, Dream, Design, Destiny) as an instrument for surfacing the pesantren's existing theological and institutional assets. The findings indicate that ecological commitment is more readily mobilised when framed as an extension of tawḥīd and fiqh al-bīʾah than when framed as an environmental obligation imported from outside; they also indicate that such commitment remains fragile, contested, and — over a short engagement — cannot be claimed as an institutionalised disposition.